The impact of prolonged violent video‐gaming on adolescent sleep: an experimental study. (9th November 2012) - King, Daniel L.; Gradisar, Michael; Drummond, Aaron; Lovato, Nicole; Wessel, Jason; Micic, Gorica; Douglas, Paul; Delfabbro, Paul
Summary: Video‐gaming is an increasingly prevalent activity among children and adolescents that is known to influence several areas of emotional, cognitive and behavioural functioning. Currently there is insufficient experimental evidence about how extended video‐game play may affect adolescents' sleep. The aim of this study was to investigate the short‐term impact of adolescents' prolonged exposure to violent video‐gaming on sleep. Seventeen male adolescents (mean age = 16 ± 1 years) with no current sleep difficulties played a novel, fast‐paced, violent video‐game (50 or 150 min) before their usual bedtime on two different testing nights in a sleep laboratory. Objective (polysomnography‐measured sleep and heart rate) and subjective (single‐night sleep diary) measures were obtained to assess the arousing effects of prolonged gaming. Compared with regular gaming, prolonged gaming produced decreases in objective sleep efficiency (by 7 ± 2%, falling below 85%) and total sleep time (by 27 ± 12 min) that was contributed by a near‐moderate reduction in rapid eye movement sleep (Cohen's d = 0.48). Subjective sleep‐onset latency significantly increased by 17 ± 8 min, and there was a moderate reduction in self‐reported sleep quality after prolonged gaming (Cohen's d = 0.53). Heart rate did not differ significantly between video‐gaming conditions during pre‐sleep game‐play or the sleep‐onset phase. Results provide evidence that prolonged video‐gaming may cause clinically significant disruption to adolescent sleep, even when sleep after video‐gaming is initiated at normal bedtime. However, physiological arousal may not necessarily be the mechanism by which technology use affects sleep.